Lithium ion battery and method for manufacturing lithium ion battery

By applying a coated portion containing Ca, Al, and La compounds to the sealing part of the lithium-ion battery, the problem of reducing corrosion resistance of the outer surface of the lithium-ion battery after the electrolyte is adhered is solved, and protection against hydrofluoric acid corrosion is achieved, and the service life of the battery is extended.

CN119836708APending Publication Date: 2025-04-15NIPPON STEEL CORPORATION

Patent Information

Application Number
CN202380063792.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-09-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The corrosion resistance of the outer surface of the lithium-ion battery is reduced after the electrolyte is adhered, especially when the sealing parts of Ni-plated steel plates or laminated steel plates are exposed to the atmosphere, which may lead to hydrofluoric acid corrosion and produce red rust.

Method used

In the sealing part of the storage case of the lithium-ion battery, especially in the part where the Fe content is 80%, a coating part containing the Ca compound, the Al compound and the La compound is used to generate fluoride by reacting with hydrofluoric acid to neutralize corrosiveness and prevent red rust from occurring.

Benefits of technology

Effectively maintain corrosion resistance of the outer surface of the lithium-ion battery, preventing hydrofluoric acid corrosion even when the electrolyte is attached, and extending the battery's service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836708A_ABST
    Figure CN119836708A_ABST
Patent Text Reader

Abstract

Even if the electrolyte is attached to the outer surface of the lithium ion battery, the corrosion resistance of the outer surface of the lithium ion battery is maintained. The present invention relates to a lithium ion battery in which a battery cell having a positive electrode, a negative electrode, and a separator, and an electrolyte solution containing a lithium salt are housed in a housing case having a main body part and a lid part, and a Ni-plated steel sheet or a laminated steel sheet is used as a blank of the housing case. In the housing case, there is at least one of a first sealing part, which is a sealing part between the main body part and the lid part, and a second sealing part, which is a sealing part between a liquid injection port lid, which seals a liquid injection port provided in the lid part, and the lid part, and at least one of the first sealing part and the second sealing part, which is a sealing part between the main body part and the lid part. The electrolyte solution is injected into the housing case through the injection port, and a coating portion containing at least one of a Ca compound, an Al compound, and a La compound is provided on a portion of the first seal portion or the second seal portion where the Fe content is 80% by mass or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium ion battery and a method for manufacturing the lithium ion battery. Background Art

[0002] In recent years, the use of secondary batteries, led by lithium-ion batteries, has rapidly expanded to power storage devices, automotive batteries, etc., which are combined with new energy systems such as solar cells and wind power generation. Therefore, lithium-ion batteries mounted on power storage devices, automotive batteries, etc., are gradually required to have higher safety. Therefore, in order to further improve the safety of lithium-ion batteries, various technologies have been proposed in recent years.

[0003] For example, the following Patent Document 1 proposes a technique for covering at least a portion of the surface of an outer casing that houses an electrode body with an insulating member. In this technique, the insulating member is provided with a non-combustible gas generating member that generates non-combustible gas at high temperatures on the side in contact with the outer casing, and the outermost layer is provided with an insulating resin layer, thereby achieving both the insulation function of the battery and the fire prevention function of the battery.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2021 / 014996 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The inventors of the present invention have come up with the following idea: In the above-mentioned lithium-ion battery, a Ni-plated steel plate having a Ni plating layer on a base steel plate or a laminated steel plate having a surface-treated layer on a base steel plate is used as a blank for a storage case that accommodates a battery cell having a positive electrode, a negative electrode and a separator, and an electrolyte containing a lithium salt.

[0009] When the Ni-plated steel sheet or laminated steel sheet described above is used as the blank of the main body and the cover of the storage case, the main body and the cover of the storage case after storing the battery cells and the electrolyte are sealed by welding represented by laser welding or riveting. In addition, depending on the situation, it is also conceivable that a liquid injection port for injecting the electrolyte into the interior of the storage case is pre-set on the cover of the storage case. In this case, after the electrolyte is injected into the interior of the main body storing the battery cells through the liquid injection port provided on the cover, the liquid injection port provided on the cover is sealed by welding or riveting using a liquid injection port cover.

[0010] Here, it is considered that when the above-mentioned electrolyte is injected, part of the electrolyte adheres to the outer surface of the main body and the cover of the storage case. The electrolyte used in lithium-ion batteries contains lithium salt (for example, LiPF 6 The lithium salt contains fluorine (such as lithium salt containing fluorine) as its component. If the lithium salt reacts with moisture in the atmosphere, hydrofluoric acid (HF) is generated. On the other hand, due to the welding process and riveting used for sealing, there is a possibility that the Ni plating layer of the Ni-plated steel plate and the surface treatment layer of the laminated steel plate partly disappear, and the parent steel plate is exposed. In addition, according to the structure of the storage shell, it is also considered that the end of the parent steel plate without the Ni plating layer and the surface treatment layer is exposed on the surface.

[0011] The inventors of the present invention have newly discovered that if hydrofluoric acid (HF) is generated in the exposed portion of such a base steel plate, the generated hydrofluoric acid corrodes the base steel plate to generate red rust, and the corrosion resistance of the outer surface of the storage case is reduced. This problem is the first problem to occur when Ni-plated steel plates and laminated steel plates are used as blanks for the main body and cover of the storage case.

[0012] The above-mentioned problem related to the corrosion resistance of the outer surface of the storage case, which was first discovered by the inventors, cannot be solved even if some research is conducted on the part that does not come into contact with the atmosphere, such as the non-combustible gas generating component disclosed in the above-mentioned Patent Document 1. Therefore, it is necessary to newly realize the following technology: even when the electrolyte adheres to the outer surface of the lithium ion battery, the corrosion resistance of the outer surface of the lithium ion battery can be maintained.

[0013] Therefore, the present invention is made in view of the above-mentioned problems, and an object of the present invention is to provide a lithium ion battery and a method for manufacturing a lithium ion battery that can maintain the corrosion resistance of the outer surface of the lithium ion battery even when an electrolyte adheres to the outer surface of the lithium ion battery.

[0014] Solutions for solving problems

[0015] In order to solve the above problems, the inventors conducted in-depth research and found that it is difficult to completely prevent the adhesion of the electrolyte, and if the battery is used, the contact between the lithium-ion battery and the moisture in the atmosphere is also inevitable. In view of the above situation, it is important to deal with the generated hydrofluoric acid. On this basis, it is considered that if a unit is provided on the outer surface of the lithium-ion battery in advance to invalidate the hydrofluoric acid generated in the reaction with the moisture in the atmosphere, the corrosion resistance of the outer surface of the lithium-ion battery can be maintained.

[0016] The gist of the present invention completed based on the above findings is as follows.

[0017] (1) A lithium ion battery, comprising a storage case having a main body and a cover, wherein a battery cell having a positive electrode, a negative electrode and a separator and an electrolyte containing a lithium salt are stored inside the storage case, wherein a Ni-plated steel sheet having a Ni plating layer provided on a base steel sheet or a laminated steel sheet having a surface treatment layer provided on a base steel sheet is used as a blank of the storage case, wherein at least one of a first sealing portion and a second sealing portion is present in the storage case, wherein the first sealing portion is a sealing portion between the main body and the cover, and the second sealing portion is a sealing portion between a liquid injection port cover and the cover, wherein the liquid injection port cover is used to seal a liquid injection port provided on the cover, wherein the liquid injection port is used to inject the electrolyte into the storage case, and wherein a coating portion containing at least one of a Ca compound, an Al compound and a La compound is present on a portion of the first sealing portion or the second sealing portion where the Fe content is 80% by mass or more.

[0018] (2) The lithium ion battery according to (1), wherein the total amount of the Ca compound, the Al compound, and the La compound in the coating portion is 0.001 g / m2 in terms of metal Ca in the case of the Ca compound, metal Al in the case of the Al compound, and metal La in the case of the La compound. 2 Above and 1000.000g / m 2 the following.

[0019] (3) The lithium ion battery according to (1), wherein in the coating portion, the Ca compound, the Al compound, and the La compound are dispersed in a resin.

[0020] (4) The lithium ion battery according to (2), wherein in the coating portion, the Ca compound, the Al compound, and the La compound are dispersed in a resin.

[0021] (5) A lithium ion battery according to any one of (1) to (4), wherein the Ca compound is at least any one of calcium carbonate, calcium oxide, and calcium hydroxide, the Al compound is at least any one of aluminum carbonate, aluminum oxide, and aluminum hydroxide, and the La compound is lanthanum carbonate, lanthanum oxide, or lanthanum hydroxide.

[0022] (6) The lithium ion battery according to (5), wherein 80% by mass or more of the Ca compound in terms of metallic Ca is calcium hydroxide.

[0023] (7) The lithium ion battery according to (5), wherein the coating portion further contains a fluoride as the Ca compound, the Al compound, or the La compound.

[0024] (8) The lithium ion battery according to (6), wherein the coating portion further contains a fluoride as the Ca compound, the Al compound, or the La compound.

[0025] (9) The lithium ion battery according to (7), wherein the fluoride is present more on the interface side with the base steel sheet constituting the Ni-plated steel sheet or the laminated steel sheet than on the surface side of the coating portion.

[0026] (10) The lithium ion battery according to (8), wherein the fluoride is present more on the interface side with the base steel sheet constituting the Ni-plated steel sheet or the laminated steel sheet than on the surface side of the coating portion.

[0027] (11) The lithium ion battery according to (7), wherein the amount of the fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

[0028] (12) The lithium ion battery according to (8), wherein the amount of the fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

[0029] (13) The lithium ion battery according to (9), wherein the amount of the fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

[0030] (14) The lithium ion battery according to (10), wherein the amount of the fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

[0031] (15) The lithium ion battery according to (1), wherein the first sealing portion and the second sealing portion are formed by welding or caulking.

[0032] (16) A method for manufacturing a lithium ion battery, wherein a battery cell having a positive electrode, a negative electrode, and a separator and an electrolyte containing a lithium salt are stored inside a storage case having a main body and a cover, wherein at least one of a first sealing portion and a second sealing portion is formed in the lithium ion battery, the first sealing portion being a sealing portion between the main body and the cover, and the second sealing portion being a sealing portion between a liquid injection port cover and the cover, the liquid injection port cover being used to seal a liquid injection port provided in the cover, the liquid injection port being used to inject the electrolyte into the storage case, and as a blank for the storage case, a base steel plate having N i is a Ni-plated steel sheet with a plating layer or a laminated steel sheet with a surface treatment layer provided on a base steel sheet, and the manufacturing method of the lithium ion battery comprises the following steps: a sealing step, for the storage shell that stores the battery unit and the electrolyte, the main body and the cover part and the liquid injection port cover and the cover part are sealed to form the first sealing part and the second sealing part; and a coating step, after the main body and the cover part and the liquid injection port cover and the cover part are sealed, a coating containing at least any one of a Ca compound, an Al compound, and a La compound is applied to a portion of the first sealing part or the second sealing part where the Fe content is 80% by mass or more.

[0033] (17) The method for producing a lithium ion battery according to (16), wherein the sealing step is performed in an atmosphere with a dew point of -75°C or less.

[0034] Effects of the Invention

[0035] As described above, according to the present invention, even when the electrolyte solution adheres to the outer surface of the lithium ion battery, the corrosion resistance of the outer surface of the lithium ion battery can be maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1A It is an explanatory diagram schematically showing a lithium ion battery in each embodiment of the present invention.

[0037] Figure 1B It is an explanatory diagram schematically showing a lithium ion battery in each embodiment of the present invention.

[0038] Figure 2A It is an explanatory diagram schematically showing a lithium ion battery in each embodiment of the present invention.

[0039] Figure 2B It is an explanatory diagram schematically showing a lithium ion battery in each embodiment of the present invention.

[0040] Figure 3It is an explanatory diagram schematically showing a raw material of a storage case for a lithium ion battery according to a first embodiment of the present invention.

[0041] Figure 4A It is an explanatory diagram schematically showing a lithium ion battery in this embodiment.

[0042] Figure 4B It is an explanatory diagram schematically showing a lithium ion battery in this embodiment.

[0043] Figure 5A It is an explanatory diagram schematically showing a lithium ion battery in this embodiment.

[0044] Figure 5B It is an explanatory diagram schematically showing a lithium ion battery in this embodiment.

[0045] Figure 6 It is an explanatory diagram schematically showing a raw material of a storage case for a lithium ion battery according to a second embodiment of the present invention.

[0046] Figure 7 It is an explanatory diagram schematically showing a raw material of a storage case for a lithium ion battery according to a third embodiment of the present invention.

[0047] Fig. 8A This is a flowchart showing an example of the flow of the method for manufacturing a lithium ion battery according to each embodiment of the present invention.

[0048] Figure 8B This is a flowchart showing an example of the flow of the method for manufacturing a lithium ion battery according to each embodiment of the present invention. DETAILED DESCRIPTION

[0049] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. In addition, in this specification and the accompanying drawings, components having substantially the same functional configuration are denoted by the same reference numerals to omit repeated description.

[0050] (About lithium-ion batteries)

[0051] <About the overall structure of lithium-ion batteries>

[0052] First, refer to Figure 1A to Figure 2B , while describing the overall structure of the lithium ion battery according to each embodiment of the present invention. Figure 1A to Figure 2B It is an explanatory diagram schematically showing a lithium ion battery in each embodiment of the present invention.

[0053] like Figure 1AAs schematically shown, the lithium ion battery 1 according to each embodiment of the present invention houses a battery cell 3 having a positive electrode, a negative electrode and a separator, and an electrolyte 5 containing a lithium salt in a housing case 10 having a main body 11 and a lid 13 .

[0054] [Regarding the battery cell 3 and the electrolyte 5]

[0055] Here, there is no particular limitation on the positive electrode (not shown), the negative electrode (not shown), the separator (not shown), and the various active materials (not shown) provided at the positive electrode and the negative electrode constituting the battery cell 3. Various components used in lithium-ion batteries can be used as appropriate for the various components constituting the battery cell 3. In addition, there is no particular limitation on the specific structure of the battery cell 3, and various structures can be adopted.

[0056] In addition, there is no particular limitation on the specific shape and size of the battery cell 3. Figure 1A In the figure, for convenience, a square-shaped battery cell 3 is illustrated, but the shape of the battery cell 3 may also be a cylindrical shape or other shapes.

[0057] In addition, the electrolyte 5 may also contain a lithium salt capable of generating lithium ions, and electrolytes containing various lithium salts (especially, lithium salts containing fluorine) may be used as appropriate. Examples of such lithium salts include LiPF 6 , LiBF 4 、LiN(SO 2 CF 3 ) 2 (Also called LiFSI.)

[0058] [About the storage case 10]

[0059] like Figure 1A As shown, the housing case 10 in the lithium ion battery 1 of the present embodiment houses the battery cells 3 and the electrolyte 5 as described above, and is composed of a main body 11 and a lid 13 .

[0060] The main body 11 of the housing case 10 is a hollow member having an internal space capable of housing the battery cells 3 and the electrolyte 5. The main body 11 is composed of a portion that becomes a bottom surface (not shown) and a portion that becomes a side surface. Figure 1A In the embodiment, the main body 11 uses a rectangular bottom surface (not shown) and four side surfaces to realize an internal space for storing the battery cells 3 and the electrolyte 5. After the battery cells 3 and the electrolyte 5 are stored in the internal space of the main body 11, as shown in FIG. Figure 1A As shown, the opening portion of the main body portion 11 is closed by a cover portion 13 .

[0061] Here, in Figure 1A The main body 11 of the housing case 10 is shown in the figure as having a square shape. However, there is no particular limitation on the specific shape of the main body 11. The main body 11 may have any shape as long as it can accommodate the battery cell 3 and the electrolyte 5.

[0062] In addition, the following situations are also considered: for example, Figure 1B As shown in FIG. 1 , a liquid injection port 15 is provided as an opening for injecting electrolyte into the storage case at a part of the cover 13A. After the electrolyte is injected, the liquid injection port 15 is closed by a liquid injection port cover 17. In the storage case 10 of this embodiment, it is also possible to use Figure 1B The cover 13A shown here is used to replace Figure 1A The cover 13 is shown.

[0063] exist Figure 1A In the storage case 10 shown in the figure, after the battery cell 3 and the electrolyte 5 are stored in the internal space of the main body 11, the opening of the main body 11 is closed by the cover 13 and sealed. As a result, the main body 11 and the cover 13 of the storage case 10 are integrated. As a result, Figure 2A In this way, the sealed storage case 10 has a sealed portion between the main body 11 and the lid 13. Figure 2A The portion indicated by the bold line in FIG. 1 is referred to as the first sealing portion 21.

[0064] In addition, Figure 1B In the storage case 10 shown in the figure, after the battery cells 3 and the electrolyte 5 are stored in the internal space of the main body 11, the opening of the main body 11 is closed by the cover 13A and sealed. In addition, the liquid injection port 15 provided in the cover 13A is closed by the liquid injection port cover 17 and sealed. As a result, the main body 11 and the cover 13A of the storage case 10 are integrated. As a result, the first sealing portion 21 is generated as a sealing portion between the main body 11 and the cover 13A, and a sealing portion between the cover 13A and the liquid injection port cover 17 is generated. Hereinafter, the "sealing portion between the liquid injection port cover and the cover portion (in Figure 2B The portion indicated by the bold line in FIG. 1 is referred to as the second sealing portion 23.

[0065] Among them, whether it is Figure 1A The storage housing 10 shown in the figure is Figure 1B When the electrolyte 5 is injected into the main body 11 in the housing case 10 as shown, part of the electrolyte 5 may adhere to the outer surfaces (portions exposed to the atmosphere) of the main body 11 and the lid 13 , 13A.

[0066] In addition, in order to determine the positions of the first sealing portion 21 and the second sealing portion 23 in the storage case 10 after the lithium ion battery has been manufactured, the following method can be used. As described above, the first sealing portion 21 is a portion where the main body 11 of the storage case 10 is sealed by the cover 13, 13A, so it is sufficient to focus on the junction between the main body and the cover of the battery cell case in the lithium ion battery of interest. In addition, as described above, the second sealing portion 23 is a portion where the injection port 15 in the cover 13A is sealed by the injection port cover 17, so it is sufficient to focus on the junction between the injection port and the injection port cover in the lithium ion battery of interest. More specifically, after the entire lithium-ion battery of interest is embedded in the resin, the entire lithium-ion battery is cut in the longitudinal direction of the battery cell casing at a position passing through the center of the short side of the lithium-ion battery, and in the case of a liquid injection port, the position passing through the center of the liquid injection port is observed in the obtained cross section using a scanning electron microscope (SEM). At this time, the size of the field of view during observation can be set to 1000μm×1000μm.

[0067] 《First Implementation Method》

[0068] <About the blank material of the storage case 10>

[0069] Next, refer to Figure 3 , while describing in detail the blank of the storage case 10 according to the first embodiment of the present invention. Figure 3 It is an explanatory diagram schematically showing a raw material of a storage case of a lithium ion battery according to the present embodiment.

[0070] A Ni-plated steel sheet or a laminated steel sheet is used as a blank material of the storage case 10 of the present embodiment. Hereinafter, a case where a Ni-plated steel sheet is used as a blank material of the storage case 10 of the present embodiment will be described.

[0071] Figure 3 1 is a diagram schematically showing the layer structure of the Ni-plated steel sheet 100 .

[0072] like Figure 3 As shown, the Ni-plated steel sheet 100 used as a raw material of the housing case 10 includes a base steel sheet 101 and Ni plating layers 103 provided on the front and back surfaces of the base steel sheet 101 .

[0073] The base steel plate 101 is a steel plate that becomes the base material of the Ni-plated steel plate 100. There is no particular limitation on the composition, metallographic structure, etc. of the base steel plate 101. As the base steel plate 101, various steel plates such as low-carbon aluminum-killed steel and IF steel (Interstitial Free Steel: ultra-low carbon steel) can be appropriately used.

[0074] In order to identify the type of the base material steel plate 101 afterwards, measurement may be performed using ICP (Inductively Coupled Plasma) emission spectrometry in accordance with JIS G 1258-1:2014.

[0075] The thickness of the base steel plate 101 may be appropriately set according to the mechanical strength required of the housing case 10 , and may be set to, for example, about 0.15 to 1.20 mm.

[0076] The Ni plating layer 103 located on the surface of the base steel plate 101 is a plating layer containing at least Ni. The Ni plating layer 103 may also be composed of Ni and impurities, and at least a portion of the Ni constituting the Ni plating layer 103 may also be alloyed with Fe derived from the base steel plate 101. There is no particular limitation on the average composition of the Ni plating layer 103. If it is a plating layer that exhibits corrosion resistance to the electrolyte 5 held in the storage case 10, various Ni plating layers, Ni alloy plating layers, etc. can be used as the Ni plating layer 103.

[0077] As the average composition of such Ni plating layer 103, for example, a composition consisting of Ni: 95-50 mass%, Fe: 5-50 mass%, and impurities can be listed. In addition, the Ni plating layer 103 may also contain any alloy element of Co, Sn, Zn, W, Mo, and Cr to replace a part of Ni. As the method for forming the Ni plating layer 103, for example, various plating methods such as hot-dip plating using a plating bath, electroplating, spraying, and vapor deposition can be listed.

[0078] The amount of Ni plating layer 103 deposited on one side is preferably 5 to 50 g / m 2 The amount of Ni plating layer 103 deposited on one side is 10 g / m 2 The above is more preferable because the corrosion resistance of the Ni-plated steel sheet 100 can be further improved. On the other hand, the amount of Ni plating layer 103 deposited on one side is 30 g / m 2 The following is more preferable because the manufacturing cost of the Ni-plated steel sheet 100 can be further reduced.

[0079] The Ni-plated steel sheet 100 may or may not be subjected to heat treatment after plating. When heat treatment is applied after plating, a diffusion alloy layer is formed at the interface between the base steel sheet 101 and the Ni plating layer 103 .

[0080] In addition, the amount of Ni plating layer 103 attached to each single side can be measured by, for example, ICP emission spectrometry. First, samples of 30 mm × 30 mm in size when viewed from above are cut out from any five locations on the bottom surface of the storage shell of the lithium ion battery of interest, and the Ni plating layer 103 present in the sample is dissolved separately using acid (more specifically, 19% hydrochloric acid). Next, the total amount of Ni contained in each solution is quantitatively analyzed using an ICP emission spectrometer (for example, ICPS-8100 manufactured by Shimadzu Corporation). The total amount of Ni presenting a value greater than 0 means that a Ni plating layer 103 is present in the obtained sample. The amount of Ni attached per unit area can be obtained by dividing the total amount of Ni obtained by the above-mentioned sample area. The average value of the five Ni attachment amounts obtained is regarded as the amount of Ni plating layer 103 attached to each single side. In addition, the average composition of the Ni plating layer 103 can also be obtained by ICP emission spectrometry. When cutting out a sample from a desired area, if the size of any side of the sample is less than 30 mm, the sample area is 90 mm. 2 The sample can be cut out from the area of ​​interest in a certain way.

[0081] In addition, in the Ni-plated steel sheet 100 described above, various chemical conversion coating layers (not shown) may be present between the base steel sheet 101 and the Ni-plated layer 103. Due to the presence of the chemical conversion coating layer, the adhesion between the base steel sheet 101 and the Ni-plated layer 103 can be further improved. In addition, due to the presence of the chemical conversion coating layer, the corrosion resistance of the Ni-plated steel sheet 100 can be further improved.

[0082] The chemical conversion coating layer is not particularly limited and may be formed by various chemical conversion treatments. Examples of such chemical conversion treatments include chromate-based chemical conversion treatments and chromate-free chemical conversion treatments. Examples of chromate-free chemical conversion treatments include chemical conversion treatments using inorganic compounds such as vanadium compounds, titanium compounds, zirconium compounds, and phosphate compounds, and silica-based chemical conversion treatments.

[0083] <Regarding the sealing process and the covering target area covered by the coating section>

[0084] Below, while referring to Figure 4A and Figure 4B The sealing process in the lithium ion battery 1 of the present embodiment and the covering target portion covered by the coating portion will be described. Figure 4A and Figure 4B It is an explanatory diagram schematically showing a lithium ion battery in this embodiment. Figure 4A1 is a diagram schematically showing a portion of a cross section of the storage housing 10 cut in the housing height direction. Figure 4B This is a diagram schematically showing a part of a cross section of the vicinity of the liquid filling port cover 17 of the storage case 10 cut in the case height direction.

[0085] In use Figure 3 When the main body 11, the cover 13, 13A, and the liquid injection port cover 17 of the storage housing 10 are manufactured using the blank shown in the figure, there is a case where the end surface of the base steel plate 101 without the Ni plating layer 103 is exposed on the surface among the various steel plates used as the blank. In addition, the main body 11 and the cover 13, 13A of the storage housing 10 and the cover 13A and the liquid injection port cover 17 are sealed by welding or riveting. At this time, there is also the possibility that part of the Ni plating layer 103 disappears due to the sealing process, and the base steel plate 101 is exposed.

[0086] Figure 4A 2 is a diagram schematically showing an example of a cross section near the first sealing portion 21. Figure 4A The shape shown is just an example, and the shape of the first sealing portion 21 and its vicinity in the lithium ion battery 1 of the present embodiment is not limited to this example.

[0087] exist Figure 4A In the example shown, the top surface of the portion that becomes the side surface of the main body 11 and the end of the cover 13 are exposed to the atmosphere as the end surface of the base steel plate 101 not provided with the Ni plating layer 103 .

[0088] Figure 4B 2 is a diagram schematically showing an example of a cross section near the second sealing portion 23. Figure 4B The shape shown is just an example, and the shape of the second sealing portion 23 and its vicinity in the lithium ion battery 1 of the present embodiment is not limited to this example.

[0089] exist Figure 4B In the example shown, at the side end of the liquid injection port cover 17, the end surface of the base material steel plate 101 is exposed to the atmosphere.

[0090] Figure 4A and Figure 4BThe portion where the end surface of the base steel plate 101 is exposed and a portion where the Ni plating layer 103 is partially lost due to the sealing process is a portion where a portion of the base steel plate 101 is exposed and the Fe content is 80% by mass or more. When manufacturing such a lithium ion battery, the portion where the end surface of the base steel plate 101 is exposed and a portion where the Ni plating layer 103 is partially lost due to the sealing process is referred to as an iron exposed portion. In the present embodiment, such a portion where a portion of the base steel plate 101 is exposed and the Fe content is 80% by mass or more is set as a covering target portion covered by the coating portion 30 as described in detail below.

[0091] The reason why the Fe content in the iron exposed portion is 80 mass % or more is as follows: That is, if a part of the Ni plating layer 103 disappears due to sealing, for example, there is a possibility that elements other than Fe derived from the Ni plating layer 103 exist in the portion.

[0092] When manufacturing the lithium ion battery 1, the members constituting the housing case 10 are subjected to a sealing 203 such as welding or caulking, resulting in an iron exposed portion on the surface of the housing case 10 that may come into contact with the atmosphere. In addition, by this sealing process, the main body 11 of the housing case 10 and the lid 13, 13A are integrated, and the lid 13A and the liquid injection port cap 17 are integrated.

[0093] <About the coating section 30>

[0094] As mentioned above, the following situation is assumed: when an electrolyte containing a lithium salt containing fluorine is injected, a part of the electrolyte adheres to the above-mentioned iron exposed portion. In this case, if the lithium salt containing fluorine reacts with moisture in the atmosphere, hydrofluoric acid is generated, and the generated hydrofluoric acid corrodes the iron exposed portion to generate red rust. Therefore, in the lithium ion battery of this embodiment, the iron exposed portion in such a sealing portion is regarded as a covering object portion 201, and a coating portion 30 is provided relative to the covering object portion 201. Therefore, from the perspective of the manufactured lithium ion battery 1, it can be said that the portion where the coating portion 30 exists is a portion regarded as the covering object portion 201 during the manufacturing process of the lithium ion battery 1.

[0095] Below, while referring to Figure 5A and Figure 5B , while describing in detail the coating portion 30 of the lithium ion battery 1 according to the present embodiment. Figure 5A and Figure 5B It is an explanatory diagram schematically showing the lithium ion battery 1 in this embodiment. Figure 5A 1 is a diagram schematically showing a portion of a cross section of the storage housing 10 cut in the housing height direction. Figure 5BThis is a diagram schematically showing a part of a cross section of the vicinity of the liquid filling port cover 17 of the storage case 10 cut in the case height direction.

[0096] like Figure 5A and Figure 5B As illustrated, in the lithium ion battery 1 of this embodiment, the coating portion 30 is provided on the covering portion 201 so as to cover the covering portion 201 (or the seal 203 present in the covering portion 201). The coating portion 30 contains at least one of a Ca compound and an Al compound.

[0097] The Ca compound, Al compound and La compound react with hydrofluoric acid (HF) to form fluoride (CaF 2 , AlF 3 、LaF 3 ), and the hydrofluoric acid can be rendered harmless. Therefore, by providing the coating portion 30 containing at least any one of the Ca compound, the Al compound, and the La compound on the covering object portion 201 (or existing on the seal 203 of the covering object portion 201), even when the electrolyte adheres to the covering object portion 201, the generated hydrofluoric acid can be rendered harmless, and the generation of red rust can be prevented. As a result, in the lithium ion battery 1 of the present embodiment, even when the electrolyte adheres to the outer surface of the lithium ion battery 1, the corrosion resistance of the outer surface of the lithium ion battery 1 can be maintained.

[0098] Here, various compounds can be used as the Ca compound, Al compound, and La compound as long as they react with hydrofluoric acid to form fluorides and the compounds themselves do not promote corrosion of the Ni-plated steel sheet 100. For example, CaCl 2 、AlCl 3 The compound was excluded from the candidate list.

[0099] Examples of such Ca compounds, Al compounds, and La compounds include hydroxides of Ca, Al, or La, salts of anions other than strong acid anions and Ca, Al, or La ions (e.g., carbonates of Ca, Al, or La), and oxides of Ca, Al, or La. Such Ca compounds, Al compounds, and La compounds are preferably compounds whose reaction products with hydrofluoric acid are not corrosive to Fe and Ni.

[0100] Examples of such Ca compounds include calcium carbonate (CaCO 3 ), calcium oxide (CaO), calcium hydroxide (Ca(OH) 2), as Al compounds, aluminum carbonate (Al 2 (CO 3 ) 3 ), aluminum oxide (Al 2 O 3 ), aluminum hydroxide (Al(OH) 3 ), as La compounds, for example, lanthanum carbonate (La 2 (CO 3 ) 3 ), lanthanum oxide (La 2 O 3 )、Lanthanum hydroxide (La(OH) 3 ). These compounds can be used alone or in combination.

[0101] In addition, in the coating portion 30, 80% by mass or more of the Ca compound contained in terms of metal Ca is preferably calcium hydroxide. The proportion of calcium hydroxide in the Ca compound is more preferably 90% by mass or more. By becoming such a state, the corrosion resistance of the outer surface at the first sealing portion 21 and the second sealing portion 23 can be further improved.

[0102] The coating portion 30 may also be formed of at least one of a Ca compound, an Al compound, and a La compound, and at least one of the Ca compound, the Al compound, and the La compound may also be formed in a state of being dispersed in a resin. When the Ca compound, the Al compound, and the La compound are dispersed in a resin, various resins can be used as a resin that functions as a binder. Examples of such resins include polyvinylidene fluoride (PVDF), epoxy resins, melamine resins, silicone resins, acrylic resins, and polyurethane resins.

[0103] The coating portion 30 of the present embodiment can be formed by preparing at least one of the above-mentioned Ca compound, Al compound, and La compound, and further preparing a treatment agent containing the above-mentioned resin as needed, applying the treatment agent to the covering target portion 201 (or the covering target portion 201 present in the seal 203), and drying it. In addition, as described again below, it is important to apply the above-mentioned treatment agent after the battery cell 3 and the electrolyte 5 are stored in the storage case 10 and the sealing process is performed, and it does not mean that the above-mentioned treatment agent can be applied before the sealing process.

[0104] In addition, for the manufactured lithium-ion battery 1, in order to determine the location where the coating portion 30 is provided afterwards, the following method can be used. First, after the entire lithium-ion battery of interest is embedded in the resin, at a position passing through the center of the short side of the lithium-ion battery, in the case of a liquid injection port, the entire lithium-ion battery is cut in the length direction of the storage shell 10 at a position passing through the center of the liquid injection port to obtain a cross-sectional observation sample. The obtained cross-sectional observation sample is appropriately ground, and the obtained cross section is observed using a scanning electron microscope (SEM). At this time, the size of the field of view during observation can be set to 1000μm×1000μm. At this time, the presence or absence of the coating portion 30 can be determined based on the difference in visual recognition results of each structure in the field of view.

[0105] In addition, in order to verify afterwards whether the coating portion 30 determined as described above is provided at a portion where the content of Fe in the first sealing portion 21 or the second sealing portion 23 is 80% by mass or more (i.e., the above-mentioned covering target portion 201), it is sufficient as follows. That is, an energy dispersive X-ray spectrometry (EDS) (e.g., JSM-7000F manufactured by JEOL Co., Ltd.) mounted on a scanning electron microscope is used to observe the cross section of the cross-sectional observation sample obtained as described above, and a mapping analysis related to the distribution of each element is performed. By comparing the cross-sectional observation results and the mapping analysis results related to, for example, the element Fe, it is possible to determine whether the coating portion 30 determined as described above is provided at a portion where the content of Fe in the first sealing portion 21 or the second sealing portion 23 is 80% by mass or more. Here, the measurement conditions for the cross-sectional observation and mapping analysis are set to an acceleration voltage of 15 kV and an irradiation current of 7.47500 nA.

[0106] In addition, in order to confirm the presence or absence of Ca compounds, Al compounds, and La compounds in the coating portion 30 afterwards, a powder sample is collected from the coating portion 30, and the obtained powder sample is analyzed by X-ray diffraction analysis. In more detail, after collecting 5 g of powder sample from an arbitrary position of the coating portion 30, it is sufficient to perform analysis using a commercially available X-ray diffraction analysis device (for example, RINT-TTR3 manufactured by RIGAKU) to confirm whether there are peaks derived from Ca, Al, and La in the measurement results. Similarly, as to whether a resin is contained in the coating portion 30, it is sufficient to confirm whether there are peaks derived from C (carbon) in the measurement results. In addition, in order to determine the compound names of the Ca compounds, Al compounds, and La compounds contained in the coating portion 30 afterwards, the compound names can be determined by assigning the peaks present in the measurement. At this time, Cu is used as the X-ray source, and the measurement conditions can be set as follows: X-ray output 50 kV, 300 mA, scanning speed 1 deg / min, step size 0.01 deg, scanning axis 2Theta / Theta, scanning range 5 to 100 deg, incident slit 1 / 2°, and length limiting slit 5 mm.

[0107] In addition, in the coating portion 30 of the present embodiment, as described above, the hydrofluoric acid is rendered harmless by reacting the Ca compound, the Al compound, and the La compound with the hydrofluoric acid, and therefore, as a product of the reaction, a fluoride of Ca, Al, or La (i.e., CaF 2 , AlF 3 、LaF 3 ). Therefore, the coating portion 30 of the lithium ion battery 1 of the present embodiment can contain fluoride as the Ca compound, Al compound, or La compound.

[0108] That is, the coating portion 30 of the lithium ion battery 1 of the present embodiment may be composed of a compound other than at least one fluoride of Ca, Al, and La, or may be composed of a compound other than at least one fluoride of Ca, Al, and La and at least one fluoride of Ca, Al, and La, or may be composed of at least one fluoride of Ca, Al, and La. Here, a powder sample is collected from the coating portion 30, and the obtained powder sample is analyzed by X-ray diffraction analysis, so that the presence or absence of fluorides of Ca, Al, or La can be confirmed. More specifically, after collecting 5 g of a powder sample from any part of the coating portion 30, an analysis is performed using a commercially available X-ray diffraction analysis device (e.g., RINT-TTR3 manufactured by RIGAKU) to confirm whether there are peaks derived from Ca, Al, La, and F in the measurement results. At this time, Cu is used as the X-ray source, and the measurement conditions can be set as follows: X-ray output 50 kV, 300 mA, scanning speed 1 deg / min, step size 0.01 deg, scanning axis 2Theta / Theta, scanning range 5 to 100 deg, incident slit 1 / 2°, and length limiting slit 5 mm.

[0109] Fluorides of Ca, Al or La are reaction products of Ca compounds, Al compounds or La compounds with hydrofluoric acid. Therefore, the fluorides are more present on the interface side with the coating target part 201 or the seal 203 than on the surface side of the coating part 30. In other words, in the coating part 30 of the present embodiment, the fluorides of Ca or Al are biased so as to be more present on the interface side with the base steel plate constituting the Ni-plated steel plate 100 or the seal 203.

[0110] In the coating portion 30, the total amount of the Ca compound, the Al compound, and the La compound deposited is preferably 0.001 g / m 2 The total deposition amount of the Ca compound, the Al compound, and the La compound is 0.001 g / m 2 As described above, the detoxification effect of hydrofluoric acid can be stably exhibited, and the corrosion resistance of the outer surfaces of the first sealing portion 21 and the second sealing portion 23 can be further improved. The total adhesion amount of the Ca compound, the Al compound, and the La compound is more preferably 100.000 g / m 2 More preferably, 300.000 g / m 2 above.

[0111] On the other hand, in the coating portion 30, the total adhesion amount of the Ca compound, the Al compound, and the La compound is preferably 1000.000 g / m2 when the total adhesion amount of the Ca compound is calculated in terms of metal Ca, the Al compound is calculated in terms of metal Al, and the La compound is calculated in terms of metal La. 2 There is also a case where the Ca compound, Al compound, and La compound are applied to the covering target portion 201 (or the seal 203 present in the covering target portion 201) in the form of a paste, so the total adhesion amount can be 1000.000 g / m 2 In addition, the total adhesion amount of the Ca compound, the Al compound, and the La compound becomes 1000.000 g / m 2 Hereby, the corrosion resistance of the outer surfaces of the first sealing portion 21 and the second sealing portion 23 can be further improved while suppressing an increase in manufacturing cost. The total amount of Ca compounds, Al compounds, and La compounds deposited also varies depending on the structure and formation method of the coating portion 30 .

[0112] For example, in the case of the coating portion 30 formed by applying at least any one of a Ca compound, an Al compound, and a La compound (i.e., a paste of the Ca compound, the Al compound, and the La compound), the total adhesion amount of the Ca compound, the Al compound, and the La compound is more preferably 800.000 g / m 2 Below, more preferably 500.000 g / m 2 In the case of the coating portion 30 formed by applying a coating material in which a Ca compound, an Al compound or a La compound is dispersed in a resin, the total adhesion amount of the Ca compound, the Al compound and the La compound is more preferably 800.000 g / m 2 Below, more preferably 500.000 g / m 2 the following.

[0113] In addition, depending on the situation, the following situation can also be considered: after the reaction between the coating portion 30 and the hydrofluoric acid is completed, the lithium ion battery is shipped after removing the excess portion. In this case, the total amount of the Ca compound, the Al compound, and the La compound can also be further preferably 100.000 g / m 2 Below left and right.

[0114] In addition, in the coating portion 30, the adhesion amount of the fluoride as the reaction product can be greater than 0 g / m 2 On the other hand, considering the amount of the electrolyte that can adhere to the first sealing portion 21 and the second sealing portion 23, the amount of fluoride that can be present in the coating portion 30 is substantially 0.200 g / m in terms of fluorine.2 the following.

[0115] Here, the total amount of Ca compounds, Al compounds, and La compounds attached to the coating portion 30 can be determined by ICP emission spectrometry. First, as a sample, a coating portion 30 of a size of 1 mm×50 mm when viewed from above is collected from any five locations, and the obtained samples are dissolved separately using sulfuric acid. Next, a commercially available ICP emission spectrometer (for example, ICPS-8100 manufactured by Shimadzu Corporation) is used to quantitatively analyze the amount of Ca, Al, and La contained in each solution. The amount of Ca, Al, and La obtained by the quantitative analysis corresponds to the converted amount in terms of Ca conversion time, the converted amount in terms of Al conversion time, and the converted amount in terms of La conversion time, respectively. Therefore, the total amount of Ca compounds, Al compounds, and La compounds attached can be obtained by dividing the sum of the obtained amount of Ca, Al, and La by the above-mentioned area. The average value of the total amount of Ca compounds, Al compounds, and La compounds attached for the five obtained amounts is regarded as the total amount of Ca compounds, Al compounds, and La compounds attached.

[0116] The adhesion amount of the fluoride in the coating portion 30 can be measured as follows.

[0117] First, as a sample, a coating portion 30 of a size of 1 mm × 50 mm when viewed from above is collected from any five locations, and the obtained samples are dissolved respectively using sulfuric acid. The gas generated during the dissolution is analyzed using a commercially available gas chromatograph (for example, Nexis GC-2030 manufactured by Shimadzu Corporation) to determine the amount of F. The amount of fluoride attached can be calculated by dividing the obtained amount of F by the above-mentioned area. The average value of the five obtained amounts of fluoride attached is regarded as the amount of fluoride attached. Thus, the amount of fluoride attached in terms of fluorine can be obtained.

[0118] In addition, the ratio of calcium hydroxide in the Ca compound contained in the coating portion 30 can be determined as follows.

[0119] That is, in the sample having the coating portion 30 containing calcium hydroxide, it is assumed that all F is combined with Ca. On this basis, the F amount is measured for the sample collected in the same manner as above. The Ca amount is converted based on the F amount obtained by the measurement and based on the above assumption. The difference between the total amount of Ca compound attached and the converted Ca amount becomes the Ca amount of calcium hydroxide. The proportion of calcium hydroxide can be calculated by dividing the Ca amount of calcium hydroxide obtained by the total amount of Ca compound attached.

[0120] In addition, for example, the biased state of the fluoride in the coating portion 30 can be confirmed as follows. First, a sample for cross-sectional observation is cut out from the coating portion 30 of the length portion of the storage shell 10. At this time, the cutting direction for obtaining the cross section is set to a direction perpendicular to the length direction of the storage shell 10. After the obtained sample for cross-sectional observation is embedded in the resin, it is appropriately ground and measured by observing the obtained cross section using a scanning electron microscope (SEM). At this time, the size of the field of view during observation can be set to 1000μm×1000μm. In more detail, the cross section of the cross-sectional observation sample obtained as described above is observed using an energy dispersive X-ray analyzer (EDS) mounted on a scanning electron microscope (for example, JSM-7000F manufactured by JEOL Corporation) and a mapping analysis related to the distribution status of each element is performed, thereby confirming the biased state of the fluoride.

[0121] At this time, in the obtained mapping result related to the element F, the situation where the position where the fluoride concentration becomes a peak is located at a position closer to the parent steel plate than the position of half the thickness of the coating portion 30 is judged as "in a biased state". Here, the measurement conditions for the mapping analysis are set to an acceleration voltage of 15 kV and an irradiation current of 7.47500 nA. In addition, regarding the thickness of the coating portion 30, the portion where the element F exists is determined based on the obtained mapping result, and the length of the determined portion is measured using the length measurement function installed in the image analysis application. Such a measurement is performed at any five locations of the cross section of interest, and the obtained measurement values ​​are averaged by the number of measurement locations, and the average value is set as the thickness of the coating portion 30.

[0122] In addition, element analysis of the coating portion 30 can also be performed by using the above-mentioned SEM-EDS analysis method.

[0123] Above, while referring to Figure 1A to Figure 5B , while describing in detail the lithium ion battery 1 of this embodiment.

[0124] 《Second Implementation Method》》

[0125] <About the blank material of the storage case 10>

[0126] Next, refer to Figure 6 , while describing in detail the blank of the storage case 10 according to the second embodiment of the present invention. Figure 6 It is an explanatory diagram schematically showing a raw material of a storage case of a lithium ion battery according to the present embodiment.

[0127] As the blank material of the storage case 10 of the present embodiment, a Ni-plated steel plate or a laminated steel plate can be used. Hereinafter, a case where a laminated steel plate is used as the blank material of the storage case 10 of the present embodiment will be described.

[0128] Figure 6 It is a diagram schematically showing the layer structure of the laminated steel plate 100A.

[0129] like Figure 6 As shown, a laminated steel plate 100A used as a blank of the housing case 10 includes a base steel plate 101 and a surface-treated layer 105 provided on the surface of the base steel plate 101 .

[0130] Here, as for the base steel plate 101 , the same base steel plate 101 as the base steel plate 101 of the Ni-plated steel plate 100 described above can be used, and therefore, detailed description thereof will be omitted below.

[0131] The surface treatment layer 105 is a layer formed by laminating the surface of the base steel plate 101 with various resins. As the surface treatment layer 105, various surface treatment layers can be applied if it exhibits corrosion resistance to the electrolyte 5 retained in the storage case 10. As the resin forming the surface treatment layer 105, for example, polypropylene (PP) resin, polyethylene terephthalate (PET) resin, polyethylene (PE) resin can be listed. These resins can be used alone or in combination.

[0132] The thickness of each single side of the surface treatment layer 105 is preferably 10 to 150 μm, for example. When the thickness of each single side of the surface treatment layer 105 is 50 μm or more, the corrosion resistance of the laminated steel sheet 100A can be further improved, so it is more preferred. On the other hand, when the thickness of each single side of the surface treatment layer 105 is 100 μm or less, the manufacturing cost of the laminated steel sheet 100A can be further reduced, so it is more preferred.

[0133] In addition, in order to determine the presence or absence of the surface treatment layer 105 afterwards, for example, ICP emission spectrometry can be used. First, samples with a size of 30 mm × 30 mm when viewed from above are cut out from any five locations on the bottom surface of the storage shell of the lithium-ion battery of interest, and the surface treatment layer 105 present in the sample is dissolved respectively using an acid (more specifically, 19% hydrochloric acid). Next, focusing on the elements that the surface treatment layer 105 may contain, each sample is quantitatively analyzed using an ICP emission spectrometer (for example, ICPS-8100 manufactured by Shimadzu Corporation). For example, focusing on the carbon (C) element contained in the resin constituting the surface treatment layer 105, the total C content contained in the dissolved solution is quantitatively analyzed. For example, since the average value of the five total C contents obtained shows a value greater than 0, it can be determined that the surface treatment layer 105 exists in the laminated steel plate 100A of interest. In addition, when cutting out a sample from a desired area, if the size of any side of the sample is less than 30 mm, the sample area is 90 mm. 2The sample can be cut out from the area of ​​interest in a certain way.

[0134] In addition, the thickness of the surface treatment layer 105 can be determined by observing the cross section of the laminated steel plate 100A using a scanning electron microscope (SEM). That is, a sample for cross-sectional observation is cut out from any part of the laminated steel plate 100A. At this time, the cutting direction for obtaining the cross section is set to the plate thickness direction of the laminated steel plate 100A. On the basis of grinding the obtained sample for cross-sectional observation, SEM photos are taken for any 5 parts of the cross section. The thickness of the surface treatment layer 105 measured in each SEM photo obtained is averaged by the number of measurement parts, and the obtained average value is set as the thickness of the surface treatment layer 105.

[0135] In addition, in the laminated steel sheet 100A described above, various chemical conversion coating layers (not shown) may be present between the base steel sheet 101 and the surface treatment layer 105. Due to the presence of the chemical conversion coating layer, the adhesion between the base steel sheet 101 and the surface treatment layer 105 can be further improved. In addition, due to the presence of the chemical conversion coating layer, the corrosion resistance of the laminated steel sheet 100A can be further improved.

[0136] Regarding the relationship between the sealing process and the covering target portion covered by the coating portion when the laminated steel plate 100A is used as the blank of the storage case 10, and the coating portion 30, in the description of the corresponding parts in the first embodiment, the description such as "Ni-plated steel plate 100" may be changed to "laminated steel plate 100A", and the description such as "Ni-plated layer 103" may be changed to "surface treatment layer 105". Therefore, hereinafter, regarding the relationship between the sealing process and the covering target portion covered by the coating portion when the laminated steel plate 100A is used as the blank of the storage case 10, and the coating portion 30, detailed description is omitted.

[0137] <<Third Embodiment>>

[0138] <About the blank material of the storage case 10>

[0139] Next, refer to Figure 7 , while describing in detail the blank of the storage case 10 according to the third embodiment of the present invention. Figure 7 It is an explanatory diagram schematically showing a raw material of a storage case of a lithium ion battery according to the present embodiment.

[0140] As a blank of the storage case 10, it is also possible to use Figure 7 As shown, a surface treated steel sheet 100B is shown in which a Ni plating layer 103 and a surface treated layer 105 are formed on the surface of a base steel sheet 101 .

[0141] Here, the Ni plating layer 103 of the surface treated steel sheet 100B has the same structure as the Ni plating layer 103 of the Ni plated steel sheet 100 of the first embodiment, and has the same effect, so the detailed description is omitted below. In addition, the surface treated layer 105 of the surface treated steel sheet 100B has the same structure as the surface treated layer 105 of the laminated steel sheet 100A of the second embodiment, and has the same effect, so the detailed description is omitted below.

[0142] In addition, in the above-mentioned surface-treated steel sheet 100B, various chemical conversion coating layers (not shown) may be present at least at any one of the positions between the base steel sheet 101 and the Ni-plated layer 103 and between the Ni-plated layer 103 and the surface-treated layer 105. Due to the presence of the chemical conversion coating layer, the adhesion between the base steel sheet 101 and the Ni-plated layer 103 and the adhesion between the Ni-plated layer 103 and the surface-treated layer 105 can be further improved. In addition, due to the presence of the chemical conversion coating layer, the corrosion resistance of the surface-treated steel sheet 100B can be further improved.

[0143] Regarding the relationship between the sealing treatment and the covering target portion covered by the coating portion and the coating portion 30 when the surface-treated steel sheet 100B is used as the blank of the storage case 10, in the description of the corresponding part of the first embodiment, the description such as "Ni-plated steel sheet 100" is changed to "surface-treated steel sheet 100B", and the description such as "Ni plating layer 103" is changed to "surface-treated layer 105, or both of Ni plating layer 103 and surface-treated layer 105". Therefore, hereinafter, the detailed description of the relationship between the sealing treatment and the covering target portion covered by the coating portion and the coating portion 30 when the surface-treated steel sheet 100B is used as the blank of the storage case 10 is omitted.

[0144] (Regarding the manufacturing method of lithium-ion battery)

[0145] Next, refer to Fig. 8A and Figure 8B , while describing an example of a method for manufacturing a lithium ion battery according to each embodiment of the present invention. Fig. 8A and Figure 8B This is a flowchart showing an example of the flow of the method for manufacturing a lithium ion battery according to each embodiment of the present invention.

[0146] Prior to the following description, it is assumed that the main body 11 and the lid 13 , 13A of the storage case 10 are manufactured in desired shapes using the Ni-plated steel sheet 100 , the laminated steel sheet 100A, and the surface-treated steel sheet 100B.

[0147] Fig. 8AA method for manufacturing a lithium-ion battery 1 in which either a first sealing portion 21 or a second sealing portion 23 exists. The first sealing portion 21 is a sealing portion between a main body portion 11 and a cover portion 13, and the second sealing portion 23 is a sealing portion between a liquid injection port cover 17 for sealing a liquid injection port 15 provided in a cover portion 13A and the liquid injection port 15.

[0148] like Fig. 8A As shown, in the manufacturing method of the lithium ion battery 1 described above, first, the battery cell 3 is stored in the storage case 10 (step S11), and then the electrolyte 5 is injected into the storage case 10 (step S13). Thereafter, the main body 11 and the lid 13 of the storage case 10, or the liquid injection port cover 17 and the liquid injection port 15 are sealed by a sealing method such as welding or riveting (step S15).

[0149] Figure 8B The present invention is a method for manufacturing a lithium-ion battery in which a first sealing portion 21 and a second sealing portion 23 exist. The first sealing portion 21 is a sealing portion between a main body portion 11 and a cover portion 13A, and the second sealing portion 23 is a sealing portion between a liquid injection port cover 17 for sealing a liquid injection port 15 provided in the cover portion 13A and the liquid injection port 15.

[0150] like Figure 8B As shown, in the manufacturing method of the lithium ion battery 1 described above, first, the battery cell 3 is stored in the storage case 10 (step S21), and then the main body 11 and the lid 13A of the storage case 10 are sealed by a sealing method such as welding or riveting (step S23). Then, the electrolyte 5 is injected into the storage case 10 through the liquid injection port 15 (step S25). Next, the liquid injection port cover 17 and the liquid injection port 15 are sealed by a sealing method such as welding or riveting (step S27).

[0151] Thus, the main body 11 and the lid 13 , 13A of the storage case 10 are integrated, and the first sealing portion 21 and the second sealing portion 23 as described above are present.

[0152] Here, various well-known methods may be appropriately adopted as to the method of housing the battery cell 3 in the housing case 10 , the method of injecting the electrolyte 5 into the housing case 10 , and the method of sealing.

[0153] However, considering the reaction between the electrolyte that can adhere to the outer surface of the storage case 10 and the moisture in the atmosphere, the steps until the step of performing the above-mentioned sealing treatment are preferably performed in an atmosphere with as little moisture as possible (for example, an atmosphere with a dew point of -75°C or less). In other words, the storage case 10 is preferably taken out into the atmosphere at least after the sealing treatment in the above-mentioned atmosphere is completed.

[0154] Next, according to the example Fig. 8A , Figure 8B The portions of the first sealing portion 21 and the second sealing portion 23 formed with an Fe content of 80 mass % or more (i.e., the covering target portion 201) are subjected to a coating process (step S17, step S29) for forming the coating portion 30. When the coating process is performed, a coating containing at least any one of the Ca compound, Al compound, and La compound described above is prepared, and the coating is applied so that the amount of adhesion after drying is within the range described above.

[0155] The coating may be a coating in which at least one of a Ca compound, an Al compound, and a La compound is dissolved or dispersed in various organic solvents, or a coating in which at least one of a Ca compound, an Al compound, and a La compound is dispersed in various resins. In addition, when an organic solvent is used, it is preferred to use carbonates contained in the electrolyte such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), and ethylene carbonate (EC).

[0156] In addition, it is preferred to carry out the coating process in an atmosphere with as little moisture as possible (for example, an atmosphere with a dew point below -75°C). From this point of view, it is further preferred to carry out the coating process of the above-mentioned coating in an atmosphere in which the above-mentioned sealing process is carried out. In addition, in the case where the coating process is carried out in an atmosphere in which moisture exists to a certain extent (for example, after the above-mentioned sealing process is completed, the sealed storage housing 10 is taken out into the atmosphere), it is preferred to carry out the coating process as quickly as possible after the sealing process.

[0157] In addition, various known coating methods can be applied to the coating target area 201 .

[0158] After the coating is applied, the applied coating is dried and cured to form the coating portion 30 on the coating target portion 201 of the lithium ion battery 1. By forming the coating portion 30, even when the electrolyte adheres to the outer surface of the lithium ion battery 1 and the lithium ion battery 1 is exposed to the atmosphere, the generation of red rust due to hydrofluoric acid can be prevented.

[0159] Furthermore, after the coating material is dried and cured, a process of removing the excess coating portion 30 may be performed as necessary.

[0160] Above, while referring to Fig. 8A and Figure 8B , while describing the method for manufacturing the lithium ion battery 1 according to each embodiment of the present invention.

[0161] Example

[0162] The lithium ion battery of the present invention will be specifically described below while showing examples and comparative examples. The examples shown below are merely examples of the lithium ion battery of the present invention, and the lithium ion battery of the present invention is not limited to the examples shown below.

[0163] (Test example)

[0164] In the test example shown below, a main body and a cover of a storage case are prepared, and the battery unit shown below is prepared, and these components are assembled to form a lithium ion battery. After the electrolyte is injected from the opening provided in the main body of the storage case, the main body is sealed with the cover, and the corrosion resistance of the outer surface of the completed lithium ion battery is evaluated.

[0165] <Main body and cover of storage case>

[0166] ◇Ni-plated steel sheet

[0167] As the Ni-plated steel sheet, a nickel-plated steel sheet (Supernickel (registered trademark)) manufactured by Nippon Steel Corporation was used. The amount of Ni deposited on one side of the nickel-plated steel sheet was 2.0 μm.

[0168] ◇Laminated steel plate

[0169] · Base material steel plate: Wuxi steel plate manufactured by Nippon Steel Corporation (Cansuper (registered trademark))

[0170] Surface treatment layer: PP (battery inner surface side (the side opposite to the battery cell)) / PET (battery outer surface side)

[0171] Resin films composed of the above-mentioned resins were prepared respectively, and the resin films were pressed against a tin-free steel plate heated to 200° C. to be fused. The thickness of the surface treatment layer after heat fusion was 50 μm.

[0172] ◇Surface treated steel plate

[0173] Also, the same surface treated layer as that provided on the laminated steel sheet was formed on the front and back surfaces of the nickel-plated steel sheet manufactured by Nippon Steel Corporation to obtain a surface treated steel sheet.

[0174] The main body and cover of the storage case are made by using the nickel-plated steel plate, the laminated steel plate and the surface-treated steel plate. Figure 1A The shapes of the main body and the cover of the storage case shown in the examples are the same.

[0175] <Battery unit>

[0176] ◇Positive plate

[0177] As the positive electrode active material, lithium cobalt oxide is used. The positive electrode active material, acetylene black and PVDF are mixed in a mass ratio of lithium cobalt oxide: acetylene black: polyvinylidene fluoride (PVDF) = 10:10:1. After that, it is applied to Al foil as an aqueous dispersion and then dried. The obtained component is rolled in a predetermined thickness, and the component cut into a predetermined size is used as a positive electrode plate.

[0178] ◇Negative plate

[0179] Amorphous carbon is used as the negative electrode active material. Amorphous carbon is dry-mixed with acetylene black as a conductive material to form a mixture. Then, N-methyl-2-pyrrolidone (NMP) dissolved with polyvinylidene fluoride is uniformly dispersed in the mixture to prepare a paste with a mass ratio of carbon: acetylene black: PVDF = 88:5:7. After the obtained paste is applied to Cu foil and dried, it is rolled in a predetermined thickness, and then the component cut out in a predetermined size is used as the negative electrode plate.

[0180] ◇Separator

[0181] A polyethylene microporous film was used as the separator.

[0182] <Electrolyte>

[0183] As the electrolyte, a solution prepared by adding 1 mol / L of lithium hexafluorophosphate to a solution prepared by mixing ethylene carbonate and diethyl carbonate at a volume ratio of 1:1 (1M-LiPF 6 EC / DEC(1 / 1)).

[0184] <Lithium-ion battery manufacturing process>

[0185] After the separator is sandwiched between the positive electrode plate and the negative electrode plate obtained as described above, they are wound to form an electrode unit. After the battery unit is flattened into a shape that can be inserted into the internal space of the main body of the storage case, the positive electrode plate is welded to the Al lead and the negative electrode plate is welded to the Ni lead. The Al lead is welded to the positive terminal provided on the cover of the storage case, and the Ni lead is welded to the negative terminal provided on the cover of the storage case.

[0186] The battery is dried in an atmosphere with a dew point of -75°C to remove moisture. Then, in the same atmosphere, the above-mentioned electrolyte is injected from the opening of the main body of the storage case. Then, the cover is fixed to the main body by welding or crimping. Then, the obtained lithium ion battery is charged at 3.6V in the same atmosphere. The water remaining in the battery is removed by electrolysis through this treatment. Then, in the same atmosphere, the same type of metal as the metal of the cover is welded to the injection port as an injection port cover to form a completed lithium ion battery.

[0187] <Corrosion resistance evaluation>

[0188] ◇Preparation of samples for evaluation

[0189] In order to simulate the condition where the electrolyte is attached to the outer surface of the lithium ion battery obtained as described above, the electrolyte (LiPF) was applied to the sealing portion between the main body and the lid (i.e., the first sealing portion) using a brush in an atmosphere with a dew point of -75°C. 6 +EC / DEC).

[0190] ◇Rust-proof treatment: Formation of coating

[0191] In an atmosphere with a dew point of -75°C, or as soon as possible after being taken out of the atmosphere, the sealing portion (first sealing portion) of the above-mentioned evaluation sample was coated with "a mixture of an organic solvent and a Ca compound, an Al compound, and a La compound", "a mixture of a resin and a Ca compound, an Al compound, and a La compound", or "only a resin" as a rust preventive agent shown in Table 1 below using a brush, and dried. Thus, a coating portion corresponding to each rust preventive agent was formed on the first sealing portion.

[0192] The Ca compound, Al compound, La compound, organic solvent, and resin used here are as follows, and are the same as commercially available general reagents.

[0193] Ca compounds: calcium hydroxide, calcium carbonate, calcium bicarbonate, calcium oxide

[0194] Al compounds: aluminum hydroxide, calcium carbonate, aluminum oxide

[0195] La compounds: lanthanum hydroxide, lanthanum carbonate, lanthanum oxide

[0196] Organic solvents: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (EC)

[0197] Resin: PVDF, epoxy resin, melamine resin, silicone resin, acrylic resin, polyurethane resin.

[0198] ◇Evaluation method

[0199] The evaluation sample after the above-mentioned rust-proof treatment was kept in an atmospheric atmosphere (i.e., in an atmosphere with moisture). The appearance was observed one month after the start of the maintenance to observe whether red rust was generated. The red rust generation rate was calculated based on the area of ​​the first sealing part and the red rust generation status obtained from the observation, and the evaluation was performed based on the following evaluation criteria. The following scores "A" to "C" were considered qualified.

[0200] Rating "A": Red rust generation rate 0%

[0201] Rating "B": Red rust generation rate is greater than 0% and less than 1%

[0202] Score "C": Red rust generation rate is greater than 1% and less than 5%

[0203] Rating "D": Red rust generation rate greater than 5%

[0204] ◇Analysis of the coating department

[0205] For each evaluation sample after confirming whether red rust was generated, a sample was collected from the coating portion. For samples corresponding to the rust preventive using an organic solvent, powder was recovered from the first sealing portion with a brush. In addition, for samples corresponding to the rust preventive using a resin, a portion of the first sealing portion was cut and recovered, and then freeze-pulverized to form a powder.

[0206] For each of the powders collected as described above, the total amount of Ca compounds, Al compounds, and La compounds attached, the ratio of calcium hydroxide to Ca compounds, the presence or absence of fluoride, and the amount of fluoride attached were analyzed according to the method described above. The ICP emission spectrometer used was ICPS-8100 manufactured by Shimadzu Corporation, and the gas chromatograph used was Nexis GC-2030 manufactured by Shimadzu Corporation.

[0207] In addition, a cross-sectional observation sample was cut out from a position different from the position where the above-mentioned powder was obtained, and the distribution state of the fluoride was confirmed according to the method described above. The cross-sectional observation sample whose fluoride peak was located at a position closer to the steel plate side than the position of half the thickness of the coating portion was evaluated as being in a "biased" state. In Table 1 shown below, the cross-sectional observation sample in a "biased" state is marked as "yes".

[0208] In addition, a cross-sectional observation sample was obtained by cutting a portion different from the portion where the above-mentioned powder was obtained using a high-speed precision cutting machine. After the obtained cross-sectional observation sample was embedded in a resin, it was wet-polished with sandpaper #1200 and further diamond-polished (Struers: DP-suspension) to finish it into a mirror surface for observation.

[0209] The obtained cross section was observed using SEM (JSM-7000F manufactured by JEOL Corporation) by using reflected electrons according to the method described above. SEM-EDS analysis was used for elemental analysis of the cross section.

[0210] <Fe mass % analysis of each seal part>

[0211] ◇Preparation of samples for analysis

[0212] Each of the main body and the cover of the housing case is produced in the same manner as the manufacturing procedure of the lithium ion battery for corrosion resistance evaluation, and then sealed in the same manner as described above. The lithium ion battery obtained by this manufacturing procedure has a first sealing portion formed in the same manner as the lithium ion battery for corrosion resistance evaluation.

[0213] ◇Analysis

[0214] Each seal was cut with a high-speed precision cutter to obtain a sample for cross-sectional observation. The obtained sample for cross-sectional observation was embedded in resin, wet-polished with sandpaper #1200, and further diamond-polished (Struers: DP-suspension) to a mirror finish for observation.

[0215] The obtained cross section was observed using SEM (JSM-7000F manufactured by JEOL Corporation) by using reflected electrons according to the method described above. SEM-EDS analysis was used for elemental analysis of the cross section.

[0216] The obtained results are collectively shown in Table 1 below.

[0217] [Table 1]

[0218] Table 1

[0219]

[0220] As is clear from Table 1, the samples corresponding to the examples of the present invention exhibited excellent outer surface corrosion resistance, whereas the samples corresponding to the comparative examples of the present invention did not exhibit excellent outer surface corrosion resistance.

[0221] The preferred embodiments of the present invention have been described in detail with reference to the accompanying drawings, but the present invention is not limited to the examples. It is obvious that a person with common knowledge in the technical field to which the present invention belongs can consider various variations or modifications within the scope of the technical ideas described in the claims, and these are of course understood to belong to the protection scope of the present invention.

[0222] The embodiments disclosed this time are illustrative in all points and are not restrictive. The above-mentioned embodiments do not depart from the structure and the main purpose of the scope of protection of the present invention described later and belong to the attached claims, and may also be omitted, replaced, and changed in various ways. For example, the constituent elements of the above-mentioned embodiments can be arbitrarily combined within the scope that does not impair their effects. In addition, of course, the functions and effects of each constituent element of the combination can be obtained from this arbitrary combination, and other functions and other effects that are obvious to those skilled in the art based on the description of this specification can be obtained.

[0223] In addition, the effects described in this specification are only for explanation or illustration and are not limiting. That is, the technology of the present invention can have other effects that are obvious to those skilled in the art based on the description of this specification together with or instead of the above effects.

[0224] In addition, the following structures also belong to the protection scope of the present invention.

[0225] (1) A lithium ion battery, wherein a battery cell having a positive electrode, a negative electrode, and a separator and an electrolyte solution containing a lithium salt are housed in a housing case having a main body and a cover.

[0226] As the blank of the storage case, a Ni-plated steel sheet having a Ni-plated layer on a base steel sheet or a laminated steel sheet having a surface-treated layer on a base steel sheet is used.

[0227] The storage case includes at least one of a first sealing portion and a second sealing portion, wherein the first sealing portion is a sealing portion between the main body and the cover, and the second sealing portion is a sealing portion between a liquid injection port cover and the cover, wherein the liquid injection port cover is used to seal a liquid injection port provided on the cover, and the liquid injection port is used to inject the electrolyte into the interior of the storage case.

[0228] A coating portion containing at least any one of a Ca compound, an Al compound, and a La compound is provided on a portion of the first sealing portion or the second sealing portion where the Fe content is 80 mass % or more.

[0229] (2) The lithium ion battery according to (1), wherein

[0230] The total adhesion amount of the Ca compound, the Al compound, and the La compound in the coating portion is 0.001 g / m2 in terms of metal Ca in the case of the Ca compound, metal Al in the case of the Al compound, and metal La in the case of the La compound. 2 Above and 1000.000g / m 2 the following.

[0231] (3) The lithium ion battery according to (1) or (2), wherein

[0232] In the coating portion, the Ca compound, the Al compound, and the La compound are dispersed in a resin.

[0233] (4) The lithium ion battery according to any one of (1) to (3), wherein

[0234] The Ca compound is at least one of calcium carbonate, calcium oxide, and calcium hydroxide,

[0235] The Al compound is at least any one of aluminum carbonate, aluminum oxide, and aluminum hydroxide,

[0236] The La compound is lanthanum carbonate, lanthanum oxide, or lanthanum hydroxide.

[0237] (5) The lithium ion battery according to any one of (1) to (4), wherein

[0238] Among the Ca compound, 80% by mass or more calculated as metallic Ca is calcium hydroxide.

[0239] (6) The lithium ion battery according to any one of (1) to (5), wherein

[0240] The coating portion further contains fluoride as the Ca compound, the Al compound, or the La compound.

[0241] (7) The lithium ion battery according to (6), wherein

[0242] The fluoride is present more on the interface side with the base steel sheet constituting the Ni-plated steel sheet or the laminated steel sheet than on the surface side of the coating portion.

[0243] (8) The lithium ion battery according to (6) or (7), wherein

[0244] The amount of fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

[0245] (9) The lithium ion battery according to any one of (1) to (8), wherein

[0246] The first sealing portion and the second sealing portion are formed by welding or riveting.

[0247] (10) A method for manufacturing a lithium ion battery, wherein a battery cell having a positive electrode, a negative electrode, and a separator and an electrolyte solution containing a lithium salt are housed in a housing case having a main body and a cover.

[0248] The lithium ion battery is provided with at least one of a first sealing portion and a second sealing portion, wherein the first sealing portion is a sealing portion between the main body and the cover, and the second sealing portion is a sealing portion between a liquid injection port cover and the cover, wherein the liquid injection port cover is used to seal a liquid injection port provided in the cover, and the liquid injection port is used to inject the electrolyte into the interior of the storage case.

[0249] As the blank of the storage case, a Ni-plated steel sheet having a Ni-plated layer on a base steel sheet or a laminated steel sheet having a surface-treated layer on a base steel sheet is used.

[0250] The manufacturing method of the lithium ion battery comprises the following steps:

[0251] a sealing step of sealing the main body and the cover and the liquid injection port cover and the cover to the housing case containing the battery cell and the electrolyte, thereby forming the first sealing portion and the second sealing portion; and

[0252] The coating step is to coat a coating containing at least any one of a Ca compound, an Al compound, and a La compound on a portion of the first sealing portion or the second sealing portion where the Fe content is 80 mass % or more after the main body portion and the lid portion and the liquid injection port cap and the lid portion are sealed.

[0253] (11) The method for producing a lithium ion battery according to (10), wherein:

[0254] The sealing step is performed in an atmosphere with a dew point of -75°C or less.

[0255] Description of Reference Numerals

[0256] 1. Lithium-ion battery; 3. Battery cell; 5. Electrolyte; 10. Storage shell; 11. Main body; 13. 13A. Cover; 15. Liquid filling port; 17. Liquid filling port cover; 21. First sealing portion; 23. Second sealing portion; 30. Coating portion; 100. Ni-plated steel plate; 100A. Laminated steel plate; 100B. Surface-treated steel plate; 101. Base steel plate; 103. Ni-plated layer; 105. Surface-treated layer; 201. Covered object portion; 203. Seal.

Claims

1. A lithium ion battery, wherein a battery cell having a positive electrode, a negative electrode and a separator and an electrolyte containing a lithium salt are housed in a housing having a main body and a cover. As the blank of the storage case, a Ni-plated steel sheet having a Ni-plated layer on a base steel sheet or a laminated steel sheet having a surface-treated layer on a base steel sheet is used. The storage case includes at least one of a first sealing portion and a second sealing portion, wherein the first sealing portion is a sealing portion between the main body and the cover, and the second sealing portion is a sealing portion between a liquid injection port cover and the cover, wherein the liquid injection port cover is used to seal a liquid injection port provided on the cover, and the liquid injection port is used to inject the electrolyte into the interior of the storage case. A coating portion containing at least any one of a Ca compound, an Al compound, and a La compound is provided on a portion of the first sealing portion or the second sealing portion where the Fe content is 80 mass % or more.

2. The lithium ion battery according to claim 1, wherein The total adhesion amount of the Ca compound, the Al compound, and the La compound in the coating portion is 0.001 g / m2 in terms of metal Ca in the case of the Ca compound, metal Al in the case of the Al compound, and metal La in the case of the La compound. 2 Above and 1000.000g / m 2 the following.

3. The lithium ion battery according to claim 1, wherein In the coating portion, the Ca compound, the Al compound, and the La compound are dispersed in a resin.

4. The lithium ion battery according to claim 2, wherein: In the coating portion, the Ca compound, the Al compound, and the La compound are dispersed in a resin.

5. The lithium ion battery according to any one of claims 1 to 4, wherein The Ca compound is at least one of calcium carbonate, calcium oxide, and calcium hydroxide, The Al compound is at least any one of aluminum carbonate, aluminum oxide, and aluminum hydroxide, The La compound is lanthanum carbonate, lanthanum oxide, or lanthanum hydroxide.

6. The lithium ion battery according to claim 5, wherein: Among the Ca compound, 80% by mass or more calculated as metallic Ca is calcium hydroxide.

7. The lithium ion battery according to claim 5, wherein: The coating portion further contains fluoride as the Ca compound, the Al compound, or the La compound.

8. The lithium ion battery according to claim 6, wherein: The coating portion further contains fluoride as the Ca compound, the Al compound, or the La compound.

9. The lithium ion battery according to claim 7, wherein: The fluoride is present more on the interface side with the base steel sheet constituting the Ni-plated steel sheet or the laminated steel sheet than on the surface side of the coating portion.

10. The lithium ion battery according to claim 8, wherein: The fluoride is present more on the interface side with the base steel sheet constituting the Ni-plated steel sheet or the laminated steel sheet than on the surface side of the coating portion.

11. The lithium ion battery according to claim 7, wherein: The amount of fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

12. The lithium ion battery according to claim 8, wherein: The amount of fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

13. The lithium ion battery according to claim 9, wherein: The amount of fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

14. The lithium ion battery according to claim 10, wherein: The amount of fluoride attached is greater than 0 g / m in terms of fluorine. 2 And 0.200g / m 2 the following.

15. The lithium ion battery according to claim 1, wherein The first sealing portion and the second sealing portion are formed by welding or riveting.

16. A method for manufacturing a lithium ion battery, wherein a battery cell having a positive electrode, a negative electrode and a separator and an electrolyte containing a lithium salt are stored in a storage case having a main body and a cover. The lithium ion battery is provided with at least one of a first sealing portion and a second sealing portion, wherein the first sealing portion is a sealing portion between the main body and the cover, and the second sealing portion is a sealing portion between a liquid injection port cover and the cover, wherein the liquid injection port cover is used to seal a liquid injection port provided in the cover, and the liquid injection port is used to inject the electrolyte into the interior of the storage case. As the blank of the storage case, a Ni-plated steel sheet having a Ni-plated layer on a base steel sheet or a laminated steel sheet having a surface-treated layer on a base steel sheet is used. The manufacturing method of the lithium ion battery comprises the following steps: a sealing step of sealing the main body and the cover and the liquid injection port cover and the cover to the housing case containing the battery cell and the electrolyte, thereby forming the first sealing portion and the second sealing portion; and The coating step is to coat a coating containing at least any one of a Ca compound, an Al compound, and a La compound on a portion of the first sealing portion or the second sealing portion where the Fe content is 80 mass % or more after the main body portion and the lid portion and the liquid injection port cap and the lid portion are sealed.

17. The method for manufacturing a lithium ion battery according to claim 16, wherein: The sealing step is performed in an atmosphere with a dew point of -75°C or less.

Citation Information

Patent Citations

  • Battery, battery pack, electronic device, electric vehicle, electricity storage device, and electric power system

    WO2021014996A1

Cited By

  • Method for detecting corrosion defect points in lithium battery

    CN120778779A